2019
DOI: 10.12968/jowc.2019.28.6.346
|View full text |Cite
|
Sign up to set email alerts
|

Real-time bacterial fluorescence imaging accurately identifies wounds with moderate-to-heavy bacterial burden

Abstract: Objective: Clinical evaluation of signs and symptoms (CSS) of infection is imperative to the diagnostic process. However, patients with heavily colonised and infected wounds are often asymptomatic, leading to poor diagnostic accuracy. Point-of-care fluorescence imaging rapidly provides information on the presence and location of bacteria. This clinical trial (#NCT03540004) aimed to evaluate diagnostic accuracy when bacterial fluorescence imaging was used in combination with CSS for identifying wounds with mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
82
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 49 publications
(114 reference statements)
6
82
0
2
Order By: Relevance
“…The current standard of care for bacterial assessment of a wound is made from subjective assessment metrics, for example swelling, odour, redness, heat, pain, all of which are host responses to high bacterial loads that vary from patient to patient. These clinical signs and symptoms have a poor predictive value 20, 21 and poor sensitivity 15,20,21 for the detection of high levels of bacteria and infection, yet they are relied upon routinely to guide decisions on where to sample, antimicrobial/antibiotic usage and the level and location of debridement. This problem is compounded in centres where patient wounds are treated by staff inexperienced with wound assessment and with little or insufficient training in complex wound care.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The current standard of care for bacterial assessment of a wound is made from subjective assessment metrics, for example swelling, odour, redness, heat, pain, all of which are host responses to high bacterial loads that vary from patient to patient. These clinical signs and symptoms have a poor predictive value 20, 21 and poor sensitivity 15,20,21 for the detection of high levels of bacteria and infection, yet they are relied upon routinely to guide decisions on where to sample, antimicrobial/antibiotic usage and the level and location of debridement. This problem is compounded in centres where patient wounds are treated by staff inexperienced with wound assessment and with little or insufficient training in complex wound care.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnostic tools can standardise care by providing objective assessment information between centres and between care providers. Multisite clinical trials with the bacterial-fluorescence imaging device, in combination with clinical signs and symptoms assessment, have increased the sensitivity for detection of moderate-to-heavy bacterial loads by three to fourfold, across multiple wound types, 15,27 facilitating evidence-based treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There is a robust body of evidence suggesting that bacterial loads at this level or greater inhibit wound healing 19 . Studies have reported high sensitivity and specificity of MLiX in detecting bacterial fluorescence in a variety of wounds including diabetic foot ulcers, venous leg ulcers, pressure ulcers, burns and surgical and trauma wounds 13,14,[18][19][20][21][22] . Information provided by fluorescence imaging on the presence and location of bacteria at loads >10 4 CFU/g is used to target cleaning, debridement, and appropriate deployment of antimicrobials 14,18 .…”
Section: Introductionmentioning
confidence: 99%